“Antique code” in Andrei Bely’s symphonies - Гармаш, Людмила Викторовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the reception of ancient mythology. The principle of antimony the Apollonian and Dionysian philosophical concepts identified as the organizing base of neo-mythological system of Andrei Bely’s early prose. The Dionysian concept was leading in Bely’s works in the early XX century, which was due to the romantic pathos of destruction generally associated with the “era of two wars and three revolutions”. The author came to the conclusion that the ancient myth is subordinate to Evangelical mythology and included in the wider paradigm of mythopoetic views of the writer: the struggle of cosmos and chaos for the World Soul.